Bahasa Inggris - Yuni K, Kusnul Ciptanila; Hidayat, Nurul; Musfiroh, Anita (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The purpose of this study is to use the Business Model Canvas (BMC) approach for resource optimization in order to build a closed-loop system-based business model for a dairy farm in Sarangan, Magetan. The methodology of this study employs a qualitative approach and descriptive analysis, incorporating field research to understand the operational conditions of the farm and in depth interviews with relevant stakeholders to collect data. This work uses BMC to design a business model that promotes both environmental sustainability and livestock operating efficiency. The findings demonstrate that implementing a closed-loop system can maximize the utilization of organic waste as feed or fertilizer, minimize resource waste, and increase the efficiency of milk production. By implementing BMC, we have discovered a business model that integrates the principles of the circular economy, enhancing value for cattle and their surrounding communities, and fostering sustainability in the long term. Consequently, this study aids in the creation of a cattle business model that is more efficient and ecologically beneficial.